WAY OF MAINTAINING THE SELF-RESPECT AS PREDICTOR OF LIFE SATISFACTION, ACADEMIC MOTIVATION AND PERSISTENCE IN ADOLESCENTS - Tamara O Gordeeva; Maria V Lunkina (Peoples' Friendship University of Russia (RUDN University), 2017)
The article deals with the problem of healthy contingencies of self-respect (self-respect based on own achievements and competence and self-respect based on others' acceptance) and neurotic contingencies of self-respect based on "pseudo-achievements". According to A. Maslow's theory of motivation, these two types of self-respect are expected to have different consequences for the psychological and school well-being of schoolchildren. The results showed that self-respect based on one's own competence, efforts, and achievements predicted psychological well-being, intrinsic and autonomous academic motivation, and persistence. Self-respect based on others' acceptance (approval) predicted only the motivation based on respect from parents and did not predict psychological well-being and persistence. Self-respect based on pseudo-achievements predicted external motivation and negatively predicted academic persistence (grit). The obtained results can serve as a basis for development of trainings which promote healthy self-respect by facilitation of personal competence development, constructive thinking, and ability to cope with difficult situations.